The way towards tailored treatment for metastatic renal cancer patients in the omics era: are we getting a “transcriptomic compass”? - Bersanelli, Melissa; Cortellini, Alessio; Buti, Sebastiano (Annals of Translational Medicine, 2019)
A transcriptome is a collection of all the gene readouts that are present in a cell. The instructions contained in the DNA of each single cell are transcribed into RNA, and the collection of the gene readouts for such transcription, the transcripts, constitute the transcriptome.